Exploring the Relationship Between Tax Reform and Tax Optimization - Empirical Research from the Accounting Professional’s Perspective - Socoliuc, Mihaela Ionela; Tulvinschi, Mihaela (The Journal of Accounting and Management, 2024)
The purpose of this research is, on the one hand, to test the perception of accounting professionals in relation to the tax measures adopted as of 01.01.2024 in Romania, and on the other hand, to identify some optimization methods agreed by accounting professionals at the level of taxation of economic agents. The research methodology is quantitative and involved testing the perceptions of accounting professionals regarding the tax reform and identifying measures of tax optimization strategies by means of a structured questionnaire, which was then statistically processed using SPSS. The results revealed that respondents do not agree with the rather high frequency of tax changes, which leads to a state of high tax unpredictability and difficulties in identifying managerial strategies for companies and, consequently, to a decrease in taxpayers’ compliance and in the collected budget revenues. We believe that the study can be useful for the state and tax regulators who can adopt tax policies aimed at increasing taxpayers’ compliance and thus reducing tax evasion, for administrators who can base their associated business strategies, but also for the academic environment that can continue research to identify new tax optimization measures in Romania.